2020
DOI: 10.20396/bjos.v19i0.8656224
|View full text |Cite
|
Sign up to set email alerts
|

Methods for caries prevention in adults among dentists from a brazilian community

Abstract: Little is known about dental practice patterns of caries prevention in adults among Brazilian dentists. Aim: To quantify procedures used for caries prevention for adult patients among dentists from a Brazilian community. Methods: Dentists (n=197) who reported that at least 10% of their patients are more than 18 years old participated in the first Brazilian study that used a translated version of the “Assessment of Caries Diagnosis and Caries Treatment” from the U.S. National Dental Practice-Based Research Netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…From these, 714 were excluded for failing to meet the other inclusion criteria, namely: 397 for participants (most studies conducted in children and adolescents; 102 for interventions; 101 because the results did not answer the research question; 114 whose study design did not fall within those recommended for a review of the literature, being mostly secondary studies). Thus, nine articles [60][61][62][63][64][65][66][67][68] were included in the study after applying quality assessment tools (k = 0.99) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From these, 714 were excluded for failing to meet the other inclusion criteria, namely: 397 for participants (most studies conducted in children and adolescents; 102 for interventions; 101 because the results did not answer the research question; 114 whose study design did not fall within those recommended for a review of the literature, being mostly secondary studies). Thus, nine articles [60][61][62][63][64][65][66][67][68] were included in the study after applying quality assessment tools (k = 0.99) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Tagliaferro et al's study [60] investigated the procedures used by dentists in a Brazilian community to prevent the carious process in adult patients. They indicated that the procedures used were pit and fissure sealants, fluoride application in the office, the recommendation to use fluoride toothpaste, mouth rinses with chlorhexidine at home, and advice to use xylitol as a replacement for sucrose in the diet.…”
Section: Findings and Contrast With The Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Dentists who chose to replace the entire defective composite restoration had lower percentages of patients interested in individualized caries prevention than dentists who chose to polish, re-surface, or repair. A possible reason for such a finding is that the patient's interest in preventive oral health may require a more-preventive approach during dental care 28 and the adoption of shared decision-making in a patient-centered care model 29 .…”
Section: Discussionmentioning
confidence: 99%